2012
DOI: 10.5578/tt.3935
|View full text |Cite
|
Sign up to set email alerts
|

ACE gene I/D polymorphism and risk of sarcoidosis development in Turkish patients

Abstract: ÖZET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…No significant differences in frequencies of I/I, I/D, D/D genotypes were observed between the sarcoidosis and control groups. Similarly, frequencies of these genotypes showed no significant differences between sarcoidosis patients with and without extrapulmonary involvement [34]. These results are in concordance with our findings in a Polish population.…”
Section: Discussionsupporting
confidence: 91%
“…No significant differences in frequencies of I/I, I/D, D/D genotypes were observed between the sarcoidosis and control groups. Similarly, frequencies of these genotypes showed no significant differences between sarcoidosis patients with and without extrapulmonary involvement [34]. These results are in concordance with our findings in a Polish population.…”
Section: Discussionsupporting
confidence: 91%
“…33 Thus, a total of 17 studies met our inclusion criteria. 1327,32,41 Two eligible studies contained data on two different sarcoidosis groups, 19,22 and these were treated independently. Thus, a total of 19 separate comparisons met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32,33,41 One study was excluded because it contained a polymorphism different from the ACE I/D polymorphism. 33 Thus, a total of 17 studies met our inclusion criteria.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ACE gene is located on the long arm of chromosome 17 at position 23.3. Even though ACE gene polymorphisms have been proven to be associated with an increased risk for cardiovascular disease [ 14 ], there is no evidence that it is associated with an increased risk of sarcoidosis [ 15 ]. Interestingly, the same study showed that there is a higher frequency of the D-allele in sarcoidosis patients compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%